The last king of Scotland - Macdonald, Kevin; Morgan, Peter; Brock, Jeremy; Calderwood, Andrea; Bryer, Lisa.; Steel, Charles; Fox Searchlight Pictures; DNA Films; FilmFour (Firm). ([London] DNA Films, 2006)
Nick Garrigan has just graduated from medical school in his native Scotland, seeking a change he travels to 1970's era Uganda with the vague but well-intentioned notion of providing aid to the impovershed locals. After aiding newly-appointed dictator Idi Amin in a car collision, Amin asks Nick to serve as his personal physician.
Based on the book : Last king of Scotland / by Giles Foden
Director of photography, Anthony Dod Mantle ; edited by Justine Wright ; music by Alex Heffes ; production designer, Michael Carlin ; costume designer, Michael O'Connor ; special effects supervisor, Sebastian Bulst ; visual effects supervisors, John Lockwood, Steve Street.
Forest Whitaker(Idi Amin), James McAvoy (Nicholas Garrigan), Kerry Washington (Kay Amin), Simon McBurney (Stone), David Oyelowo (Dr. Junju), Stephen Rwangyezi (Jonah Wasswa), Abby Mukiibi (Masanga), Adam Kotz (Dr. Merrit), Gillian Anderson (Sarah Merrit).
MPAA rating: Rated R.
VCD.
Keywords: Dictators -- Uganda -- Drama; Physician and patient -- Uganda -- Drama; Genocide -- Uganda -- Drama